Programa de intervención virtual para afrontar el impacto del COVID-19 sobre la salud mental en trabajadores de emergencia de un hospital privado - Lima 2022 - Palomino Basagoitia, Carlos Alberto (2024)
Objective: To determine the differential effectiveness of an intervention program aimed at reducing the impact on mental health (anxiety, stress and depression) by COVID-19 in emergency workers of a private hospital in the year 2022. Methodology: It was a quantitative, descriptive, cross-sectional, prospective and quasi-experimental approach research pre and post test with control group. The sample consisted of 52 emergency workers from a private hospital (the same as the population) in which the DASS 21 questionnaire was administered for diagnosis of mental health compromise (anxiety, stress and depression); then the four-session program was carried out in the intervention group and the instrument was administered again to both groups. Student's t test was used to compare the results of levels of anxiety, stress and depression after the intervention. Results: It was found that 40.4% of the health workers participating in the study (52) had some degree of anxiety, 17.3% some degree of stress and 5.8% some degree of depression. After the application of the program in the intervention group, there was a difference in the mean levels of anxiety (6,81 -3,08), stress (5.31-1.69) and depression (2.50-1,50); this difference was statistically significant for anxiety and stress levels (p < 0.05). Conclusions: The results reveal a differential effectiveness of the proposed program that is evident in the benefit acquired by the workers with commitment to anxiety, stress and depression participating in the program; which is reflected in the change observed in the measurement of anxiety, stress and depression evaluated with the DASS-21 instrument applied after the program.